MERETAS JALAN MEMBERDAYAKAN PENDIDIKAN ISLAM - Agus Sholeh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2006)
The expenditure of madrasah (Islamic Education Institution) as naÂtional education subsystem has various consequences which are not simple, mainly on the pattern of education that must use one measureÂment, Department of National Education Affairs. The impact of it to madrasah is the appearing of obstacles and anomalies. It seems fifteen years since the application of National Educational System Law (UU SPN) year 1989, the government has not able yet to uplift the image of madrasah as an alternative of education institution. The question: What are needs to be done next by Department of Religious Affairs?